Effectiveness of a multimodal intervention in functionally impaired older people with type 2 diabetes mellitus. Issue 4 (23rd April 2019) - Rodriguez‐Mañas, Leocadio; Laosa, Olga; Vellas, Bruno; Paolisso, Giuseppe; Topinkova, Eva; Oliva‐Moreno, Juan; Bourdel‐Marchasson, Isabelle; Izquierdo, Mikel; Hood, Kerry; Zeyfang, Andrej; Gambassi, Giovanni; Petrovic, Mirko; et al.
Abstract: Background: Type 2 diabetes, a highly prevalent chronic disease, is associated with increasing frailty and functional decline in older people. We aimed to evaluate the effectiveness of a multimodal intervention on functional performance in frail and pre‐frail participants aged ≥70 years with type 2 diabetes mellitus. Methods: The MID‐Frail study was a cluster‐randomized multicenter clinical trial conducted in 74 trial sites across seven European countries. The trial recruited 964 participants who were aged >70 years [mean age in intervention group, 78.4 (SD 5.6) years, 49.2% male and 77.6 (SD 5.29) years, 52.4% male in usual care group], with type diabetes mellitus and determined to be frail or pre‐frail using Fried's frailty phenotype. Participants were allocated by trial site to follow either usual care (UCG) or intervention procedures (IG). Intervention group participants received a multimodal intervention composed of (i) an individualized and progressive resistance exercise programme for 16 weeks; (ii) a structured diabetes and nutritional educational programme over seven sessions; and (iii) Investigator‐linked training to ensure optimal diabetes care. Short Physical Performance Battery (SPPB) scores were used to assess change in functional performance at 12 months between the groups. An analysis of the cost‐effectiveness of the intervention was undertaken using the incremental cost‐effectiveness ratio (ICER). Secondary outcomes included mortality, hospitalization, institutionalization, quality of life, burden on caregivers, the frequency and severity of hypoglycaemia episodes, and the cost‐effectiveness of the intervention. Results: After 12 months, IG participants had mean SPPB scores 0.85 points higher than those in the UCG (95% CI, 0.44 to 1.26, P < 0.0001). Dropouts were higher in frail participants and in the intervention group, but significant differences in SPPB between treatment groups remained consistent after sensitivity analysis. Estimates suggest a mean saving following intervention of 428.02 EUR (2016) per patient per year, with ICER analysis indicating a consistent benefit of the described health care intervention over usual care. No statistically significant differences between groups were detected in any of the other secondary outcomes. Conclusions: We have demonstrated that a 12 month structured multimodal intervention programme across several clinical settings in different European countries leads to a clinically relevant and cost‐effective improvement in the functional status of older frail and pre‐frail participants with type 2 diabetes mellitus.